Land and water management in Southern Africa towards sustainable agriculture - Africa Institute of South Africa (pretoria Africa Institute of South Africa, 2008)
The Southern African Development Community (SADC) and its Member States are making renewed efforts to revive agriculture in the region. Given that much of it is water-stressed, appropriate and sustainable land and water management practices are vital to achieving this objective. Recognising this, SADC's Land and Water Management Applied Research and Training Programme has convened two scientific symposiums. Held in Lilongwe, Malawi, in February 2006, the inaugural symposium brought together R&D practitioners from 10 participating SADC countries to deliberate on land and water management for sustainable agriculture, and discuss how the most recent research and development advances in land and water management might be made more relevant to policy-makers as well as the region's small-scale farmers. The edited contributions to the first symposium appear in this volume. The second symposium was held in Gaborone, Botswana, in February 2007, and brought together regional experts to discuss opportunities for improving water use and water use efficiency in agriculture in semi-arid and arid areas. The edited contributions to the second symposium appear in a companion volume entitled Land and Water Management in Southern Africa: Towards Better Water Use in Agriculture in Semi-Arid and Arid Areas (AISA 2008). It is hoped that these two volumes will help to disseminate regional expertise on land and water management to a wider audience, thus helping policy-makers and others to strengthen the agricultural sector in the region, and, in so doing, improve its food security and the wellbeing of its people.
Includes index
Keywords: Sustainable agriculture--Africa, Southern